Experiment on the continuous recovery of H2 from hydrogenation plant off-gas via hydrate formation in tetra-n-butyl ammonium bromide solution. (14th December 2015) - Luo, Yang; Liu, Aixian; Guo, Xuqiang; Sun, Qiang; Yang, Lanying
Abstract: Here, an approach toward for continuous H2 recovery from hydrogenation plant off-gas based on hydrate formation in the presence of tetra-n-butyl ammonium bromide (TBAB) is proposed. Firstly, we explored the conditions to form the CH4 /H2 /TBAB hydrate through pressure search method in the single-stage equilibrium separation experiments toward CH4 /H2 mixture. The influence of initial pressure, temperature, and initial gas–liquid volume ratio were systematically optimized in the context of 10 wt% TBAB solution. Then, we conducted the continuous separation experiments of CH4 /H2 binary mixture and hydrogenation plant off-gas using a set of laboratory-scale continuous stirred reactor according to the optimized conditions, in which the effects of pressure and liquid flow rate upon continuous separation were further studied. The experimental results that the H2 concentration in the unhydrated gas (the recovered gas) is up to 89 mol% and the yield of H2 recovery is more than 58.68% indicate the efficiency to recover H2 using continuous hydrate separation, which lays the foundation for further industrial application. Highlights: We explored the condition to form CH4/H2/TBAB hydrate. One stage equilibrium hydrate separation of CH4/H2 mixture was conducted. We achieved continuous H2 recovery from plant off-gas via hydrate formation. We investigated the influences of pressure, temperature and gas-liquid volume ratio. The gas storage capacity of hydrate was investigated.